1976
DOI: 10.1136/jmg.13.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Classification and relationships of induced chromosomal structual changes.

Abstract: Summary. A detailed survey is given ofthe types and classification of primary structural changes that can be induced in chromosomes and observed at the first metaphase after the initial damage. Comments upon identification and scoring are given for the benefit of new workers. The annotation concludes with a brief discussion of the potential relationships between the primary types, and the secondary or derived types encountered in clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
243
1
4

Year Published

1986
1986
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 514 publications
(254 citation statements)
references
References 33 publications
6
243
1
4
Order By: Relevance
“…Radiation induces chromosome-type aberrations; however, chemical substances generally induce chromatid-type aberrations. These phenomena may be explained by the facts that damage to DNA induced by a chemical substance is still not immediately reflected and that CAs appear only after DNA undergoes a synthetic period (26). In this study, many chromatid-type aberrations were found to occur due to exposure to the chemical substance (N-MDMA), and the ratio of exchange-type chromatid aberrations out of all chromosomes or chromatid aberrations increased.…”
Section: Discussionmentioning
confidence: 57%
“…Radiation induces chromosome-type aberrations; however, chemical substances generally induce chromatid-type aberrations. These phenomena may be explained by the facts that damage to DNA induced by a chemical substance is still not immediately reflected and that CAs appear only after DNA undergoes a synthetic period (26). In this study, many chromatid-type aberrations were found to occur due to exposure to the chemical substance (N-MDMA), and the ratio of exchange-type chromatid aberrations out of all chromosomes or chromatid aberrations increased.…”
Section: Discussionmentioning
confidence: 57%
“…This effect was previously recorded by Abderrhman (1998) and Banerjee (1992) for Peganum harmala and tobacco extracts respectively. The present effect of Calotropis extract is probably due to direct effect on viscosity of the protoplasm and DNA proteins of the chromosomes as stated by Savage (1975) and Abderrhman (1998).…”
mentioning
confidence: 85%
“…Another class of anomalies observed is chro mosomal stickiness which is also induced by several agricultural chemicals (Grant 1978). Stickiness is generally regarded as a physiological effect on chromosomes during division (Savage 1975) and has been considered as a category of chromatid aberration (Klasterska et al 1976). The third class of chromosomal anomalies produced by turbutryn is chromosome aberrations including chromosome breakage.…”
Section: Methodsmentioning
confidence: 99%